EFFECT OF SUSTAINABILITY DISCLOSURE ON FINANCIAL PERFORMANCE OF LISTED MANUFACTURING FIRMS IN NIGERIA - Oloyede Deborah Elaitan; Saidu Ibrahim Halidu, Ph.D.; UYAGU John Benjamin; Abdullahi Ya'u Usman (Gusau Journal of Accounting and Finance, 2025)
Manufacturing companies in Nigeria are increasingly expected to disclose their sustainability practices, but the financial benefits of doing so are still uncertain. This study explored how different aspects of sustainability reportingeconomic, environmental, and socialrelate to the financial performance of listed manufacturing firms, focusing on return on equity. Using a quantitative research method, the study collected secondary data from the audited annual reports of 10 manufacturing firms listed on the Nigerian Stock Exchange, covering the years 2020 to 2022. These firms were chosen based on their consistent publication of financial and sustainability reports during this period. The data were analyzed using multiple regression analysis to understand the effect of each sustainability component on profitability. The results of the study showed that economic and environmental disclosures were linked to lower financial performance, while social disclosures had no significant impact. However, when all three aspects were considered together, they showed a combined positive effect on profitability. This suggests that companies may hesitate to report sustainability information unless it clearly improves performance. The study recommends that firms adopt a complete and balanced approach to sustainability reporting, as it is more likely to gain support from stakeholders and contribute to long-term business success.